Kinetics of Gliserolysis Reaction of Silkworm Pupae Oil on Synthese Surfactant Biodegradable. Issue 1 (February 2021) - Purwaningtyas, Ery Fatarina; Kasmiyatun, Mega
Abstract: Continuing previous research entitled "The Innovation of Making MAG-DAG Biodegradable Surfactants Based on Silkworm Waste: Raw Material for Animal Oil". So this study aims to determine the kinetics of the reaction. Determining the order of the reaction can only be done experimentally, the second-order reaction is not always bimolecular, but the bimolecular reaction must be of second order. The reaction is carried out at various temperature variations namely 65°C, 75°C, and 85°C at 1 atm pressure. Each interval of one hour, samples were taken from the process up to 4 hours of reaction time, to then be analyzed the residual content of triglycerides in each sample. The results showed that the higher the reaction temperature, the faster the reaction. Further analysis showed that the reaction that occurred was an alternating second-order reaction, the deviation was respectively 8.84% and 16.71%, with the values of k1 and k2 : k 1 = 1, 1625 × 10 5 exp ( − 6946, 06 T ) ( L mol .s ) k 2 = 7, 4306 exp ( − 4038, 74 T ) ( L mol .s ) The general equation for the reaction speed of pupa oil glycerolysis is r = k1 (CA ) (CB ) – k2 (CC ) (CD )